European guideline on indications, performance and clinical impact of 13C‐breath tests in adult and pediatric patients: An EAGEN, ESNM, and ESPGHAN consensus, supported by EPC. Issue 5 (14th June 2021) - Keller, Jutta; Hammer, Heinz F.; Afolabi, Paul R.; Benninga, Marc; Borrelli, Osvaldo; Dominguez‐Munoz, Enrique; Dumitrascu, Dan; Goetze, Oliver; Haas, Stephan L.; Hauser, Bruno; Pohl, Daniel; Salvatore, Silvia; et al.
Abstract: Introduction: 13 C‐breath tests are valuable, noninvasive diagnostic tests that can be widely applied for the assessment of gastroenterological symptoms and diseases. Currently, the potential of these tests is compromised by a lack of standardization regarding performance and interpretation among expert centers. Methods: This consensus‐based clinical practice guideline defines the clinical indications, performance, and interpretation of 13 C‐breath tests in adult and pediatric patients. A balance between scientific evidence and clinical experience was achieved by a Delphi consensus that involved 43 experts from 18 European countries. Consensus on individual statements and recommendations was established if ≥ 80% of reviewers agreed and <10% disagreed. Results: The guideline gives an overview over general methodology of 13 C‐breath testing and provides recommendations for the use of 13 C‐breath tests to diagnose Helicobacter pylori infection, measure gastric emptying time, and monitor pancreatic exocrine and liver function in adult and pediatric patients. Other potential applications of 13 C‐breath testing are summarized briefly. The recommendations specifically detail when and how individual 13 C‐breath tests should be performed including examples for well‐established test protocols, patient preparation, and reporting of test results. Conclusion: This clinical practice guideline should improve pan‐European harmonization of diagnostic approaches to symptoms and disorders, which are very common in specialist and primary care gastroenterology practice, both in adult and pediatric patients. In addition, this guideline identifies areas of future clinical research involving the use of 13 C‐breath tests.